Pollen cargo structure on Aculeata – visitors of alien Solidago canadensis L. s. l. inflorescences in Belarus - Koroteeva, Daria O.; Sheiko, Anna A. (Experimental Biology and Biotechnology, 2022)
Community structure of visitors to inflorescences of invasive goldenrods was investigated by sampling at 9 sites in Minsk city, Minsk and Mogilev regions in Belarus. A total 44 species of Aculeata including 1 species of Chrysioidea, 7 species of Vespoidea and 36 species of Apoidea were registered. Among them 2 species of bumblebees (Bombus terrestris L., B. lapidarius L.) were numerous, 2 species of Vespoidea (Polistes dominula Christ, P. nimpha Christ) and 3 species of Apoidea (Philanthus triangulum F., Hylaeus communis Nyl., B. ruderarius Müller) were common. Pollen cargo analysis revealed the predominance of easily lost and relatively easily lost conspecific pollen grains on the bodies of the imago of the all common and numerous species of visitors to inflorescences of invasive goldenrods.
Keywords: pollen cargo analysis; pollination; Apoidea; Vespoidea; anthophilous insects; pollinator communities